Evaluasi Pelaksanaan Program Praktikum Metodologi Penelitian dengan Model Countenance di Fakultas Agama Islam Universitas Muhammadiyah Jakarta - Romlah Gani (At-Tajdid: Jurnal Ilmu Tarbiyah, 2019)
The research in practic is the next step of course after mastering research methodology theory. It is design and applied to the studentthe ability of proposing thesis to campus through some phases proposal form. The evaluation of research in practices is necessary to be applied to achieve effective program maximally and having positive impact to person involved. The research uses qualitative approach and case studymethod. Stake’s countenance model is applied for this evaluation model, with developed by Robert E. Stake (1975) with antecedents, transactions, and outcomes for is phase. Each phase consist of description and judgment. The criteria of evaluation is set based on discussion with the stakeholder andfiedelityresults. The collection of data techniqueusiparticipant observation, indepth interview, and document check. The Validation and checking data techniqueuse triangulation.The source of data involves the board of FAI UMJ, the lecturers as menthor, the student inprogramparticipant, and staff, and academic document. The data analysis technique uses qualitative model developed by Miles & Huberman (1984) consist data reduction,data display, and conclusions/verification. In the antecedence phase of this practice research program consist of some aspects such as curriculum, students, persons, and tools. In this phase, the program is high effective. The transaction phase consist of some aspects such as planning, program implementations, reporting, monitoring and evaluation. In this phase the program is moderate effective.in the outcome phase consists of some aspects such as the result of learning and the effect of scholarship for students.in this phase, the program is moderate effective. As the conclution of the practice research program is effective enough to elevate the aility of students in creating proposal.